Management of Parents’ Role in Children of the Early Childhood Education of Al-Palah Batang Asai Jambi - Sodiah Sodiah; Habel Habel (INNOVATIO: Journal for Religious Innovation Studies, 2020)
A good parent-children relationship is an understanding relationship with guidance. Parents have a big influence develop children's abilities in the school environment. The research objective is to determine the role of parents in PAUD Al-Palah Batang Asai Jambi in encouraging children's development. The research method used is a qualitative method with a case study approach, where observation and interview techniques are used. The results showed that the role of parents in the development of PAUD Al-Palah Batang Asai Jambi children in terms of communication is still dominated by parents. The encouragement given was based on the wishes of parents who focus on cognitive children, not the children's needs, and parents tend to generalize the children's ability which naturally different from each other. Involving parents in schools in the form of caring and sharing which has been carried out through mentoring children to practice outside of school, meeting visits, discussion of child development with teachers, and parents as good role models for children. Therefore, the role of parents must be increased through a system of school-parent relationships. Hubungan orang tua dengan anak yang baik adalah hubungan yang penuh pengertian disertai bimbingan. Orang tua memberikan pengaruh besar untuk mengembangkan kemampuan anak di lingkungan sekolah. Tujuan penelitian untuk mengetahui peranan orang tua di PAUD Al-Palah Batang Asai Jambi dalam mendorong perkembangan anak. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan studi kasus sehingga mengunakan teknik pengamatan dan wawancara. Hasil penelitian menunjukkan bahwa peran orang tua pada perkembangan anak PAUD Al-Palah Batang Asai Jambi dalam komunikasi masih didominasi oleh orang tua, dorongan yang diberikan berbasis keinginan orang tua yang terpusat pada kognitif anak bukan child need, dan pemahaman orang tua menyamaratakan kemampuan anak yang secara alamiah berbeda setiap individunya. Pelibatan orang tua di sekolah berbentuk caring dan sharing yang telah dilakukan melalui pendampingan anak praktik di luar sekolah, kunjungan rapat, diskusi perkembangan anak dengan guru, dan orang tua sebagai role model yang baik bagi anak. Maka peran orang tua harus ditingkatkan melalui sistem hubungan kerjasama sekolah dengan orang tua.